Barrido del haz en antena de onda de fuga basada en metasuperficie mediante cristales líquidos - Abdo-Sánchez, María Elena; Epstein, Ariel; Eleftheriades, George V. (Iñigo Cuiñas Gómez, 2021)
In this communication, the reconfigurability mechanisms for beam steering at a fixed frequency in a leakywave antenna based on Huygens metasurfaces are reviewed. A preliminary design for a forward-to-backward scanning antenna at 24 GHz is proposed based on the use of a commercial liquid crystal (er ranging from 2.46 to 3.54). The simulation results show that the beam steers when the permittivity of the liquid crystal (partially filling the waveguide, with a 560 um high layer) is reconfigured. It is shown that the antenna can meet the challenges of this technology (a very thin layer of liquid crystal and a not very wide range of permittivity) while obtaining scanning from -15 to 15º maintaining the directivity around 17 dBi, including broadside.
Este trabajo ha sido financiado por el Ministerio de Ciencia, Innovación y Universidades (MCIU) (Contrato Juan de la Cierva-Incorporación) bajo el contrato IJC2018-038440-I y por el MCIU/AEI/FEDER (Programa Estatal de I+D+i Orientada a los Retos de la Sociedad) bajo el proyecto RTI2018- 097098-J-I00.
Keywords: Antenas; Cristal líquido; Antena; Metasuperficie; Reconfiguración